PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOTOR YAMAHA PADA PRODI MANAJEMEN UNIVERSITAS STIKUBANK SEMARANG (Students' Journal of Economic and Management, 2015)
Competition in the business world today is getting tougher, with new businesses coupled with business actors increasingly making today's competitive business has a high determination. The purpose of this study is to investigate, analyze, and explain the products and promotions on purchasing decisions Yamaha in Student Management Prodi Stikubank University of Semarang, and to know whether the products and promotions positive influence on purchase decisions in Student Management Prodi Stikubank University of Semarang. The population studied is the Student Management Prodi Stikubank University of Semarang with the number of 719 students, the samples were taken as 125 people were made respondents using Slovin formula. Data collected was tested first using validity and reliability in order to obtain reliable results valit and so can be used in subsequent testing. Subsequent analysis the authors used multiple regression testing to clarify the relationship between the independent variables and the dependent variable. The result is a product and promotion of a positive influence on purchase decisions. From the results of the regression equation that promotion has pengeruh greatest and most products have little effect. The results of determination test and promotional products derived variables in explaining the relatively large purchase decision. This study has limitations that variable is used only in the variable products and promotions, whilst still much that can influence purchasing decisions. In addition, this study only examined the students who use the Yamaha at the University of Semarang especially Prodi Management Stikubank further recommended to consider other variables that have not been found in this study and a broader sampling. Keywords: product, promotion and purchasing decisions.